Anatomy of the accessory mental foramen in a Saudi subpopulation: A multicenter CBCT study - Fahd Aljarbou; Abdullah M. Riyahi; Abdullah Altamimi; Abdullatif Alabdulsalam; Nasser Jabhan; Mazen Aldosimani; Hadi M. Alamri (Elsevier, 2021)
Aim: The aim of this is to evaluate the prevalence and location of the accessory mental foramen (AMF) in a Saudi population using cone-beam computed tomography (CBCT). Methodology: CBCT data were retrieved from two dental facilities at two universities located in two different cities and filtered over a period of four years. The scans were aligned when the AMF was noticed, and then the size of both the AMF and mental foramen (MF), its location, and the distance from the AMF to the MF were recorded. The AMF measurements were compared between males and females and between the two sides of the mandible. Results: In total, 603 CBCT scans were investigated. The percentage of scans with an AMF was 9.95% (n = 60), and AMFs were almost equally distributed on both sides. Only four cases (0.66%) of a second AMF were detected among the scans. The MFs on both sides were significantly larger in males than in females (P > 0.05), but they showed no differences in the sizes of the AMFs. The AMFs were most commonly located inferior and posterior to the MF. The distance between the MF and AMF ranged from 2.32 to 5 mm. Conclusions: The prevalence of the AMF in this Saudi population was 9.95%, and it was significantly more prevalent in males than in females. Its proximity to the MF makes it clinically important to conduct proper detailed planning prior to performing any procedure that might risk the vital structures.